PRICE REPORTING in A THIN MARKET - Ajewole, Kayode; Schroeder, Ted C.; Parcell, Joe (My University, 2017)
Thin markets create challenges for reporting market information by the U.S. Department of Agriculture (USDA) and for users of the information. This study examines distributions of transactions comprising daily price reports in the U.S. hog market. We determine publicly reported daily prices are sensitive to which packing plants buy hogs. Transaction prices comprising USDA Agricultural Marketing Service price reports are not normally distributed; care must be taken in reporting and interpreting transaction prices. Economically important variations in prices occur because of packer-specific indicators. Daily reported prices are used as base prices in marketing agreements, making variation of even greater importance. Copyright © The Author(s) 2016.
Citation: Ajewole, K., Schroeder, T. C., & Parcell, J. (2016). PRICE REPORTING in A THIN MARKET. Journal of Agricultural and Applied Economics, 48(4), 345-365. doi:10.1017/aae.2016.19
Keywords: Hog Prices; Price Reporting; Thin Markets